Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Ecogenomics and limnological dynamics of a new Thiocapsa species blooming in the whole water column of a karstic lake - Pedro J. Cabello‐Yeves; Antonio Picazo; Carlos Rochera; Daniel Morant; Eduardo Vicente; David J. Scanlan; Richard J. Puxty; Antonio Camacho (Limnology and Oceanography, 2025)
Purple sulfur bacteria (PSB) of the family Chromatiaceae (Gammaproteobacteria) can perform chemo‐ and photo‐lithoautotrophy (through anoxygenic photosynthesis) in anoxic layers of freshwater stratified (including meromictic) lakes. This group has been extensively studied via physiological and ecological approaches, albeit their genomics has lagged behind. Here, we monitored a small, shallow, karstic lake, Lagunillo de Cardenillas, that developed a pink coloration throughout the whole water column and prevailed for ca. 2 years across seasons of the limnological cycle. Combining the study of physical/chemical parameters, amplicon sequencing, metagenomics, genomics, and microscopy, we observed this phenomenon was caused by blooms of a novel Thiocapsa species, which represented ca. 40% of the total microbial biomass of the lake's water column during the autumn/winter mixing period, and ca. 36% in the anoxic layers during spring/summer stratification. The dominance of this microbe was attributed to the high sulfur concentrations and biogeochemical features of the lake combined with various genomic footprints/abilities of this microbe to utilize different nutrient sources under anoxic and oxic/microaerophilic conditions. The latter included nitrogen (cyanate and ethanolamine hydrolysis, N fixation, dissimilatory nitrate reduction, ammonia assimilation, denitrification), carbon (anoxygenic photosynthesis and the presence of α‐carboxysomes and type IA RuBisCOs) and sulfur (dimethylsulfide [DMS] and thiosulfate oxidation, dimethylsulfoxide [DMSO] reduction). In addition, this novel species possessed genes for gas vesicle formation, anoxic/oxic respiration pathways, hydrogenases, oxic stress response, and a CRISPR‐Cas array. Thus, its extensive genomic repertoire helped explain its versatility and success in colonizing both the anoxic layers and the oxic/anoxic interphase in this lake.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Membrane lipid renovation in Pseudomonas aeruginosa ‐ implications for phage therapy? - Rhiannon Lyon; Rebekah A. Jones; Holly Shropshire; Isabel Aberdeen; David J. Scanlan; Andrew Millard; Yin Chen (Environmental Microbiology, 2022)
Pseudomonas aeruginosa is an important Gram‐negative pathogen with intrinsic resistance to many clinically used antibiotics. It is particularly troublesome in nosocomial infections, immunocompromised patients, and individuals with cystic fibrosis. Antimicrobial resistance (AMR) is a huge threat to global health, with a predicted 10 million people dying from resistant infections by 2050. A promising therapy for combatting AMR infections is phage therapy. However, more research is required to investigate mechanisms that may influence the efficacy of phage therapy. An important overlooked aspect is the impact of membrane lipid remodelling on phage binding ability. P. aeruginosa undergoes changes in membrane lipids when it encounters phosphorus stress, an environmental perturbation that is likely to occur during infection. Lipid changes include the substitution of glycerophospholipids with surrogate glycolipids and the over‐production of ornithine‐containing aminolipids. Given that membrane lipids are known to influence the structure and function of membrane proteins, we propose that changes in the composition of membrane lipids during infection may alter phage binding and subsequent phage infection dynamics. Consideration of such effects needs to be urgently prioritised in order to develop the most effective phage therapy strategies for P. aeruginosa infections.

Microbial uptake dynamics of choline and glycine betaine in coastal seawater - Michaela A. Mausz; Ruth L. Airs; Joanna L. Dixon; Claire E. Widdicombe; Glen A. Tarran; Luca Polimene; Sarah Dashfield; Rachael Beale; David J. Scanlan; Yin Chen (Limnology and Oceanography, 2022)
Choline and glycine betaine (GBT) are utilized as osmolytes to counteract osmotic stress, but also constitute important nutrient sources for many marine microbes. Bacterial catabolism of these substrates can then lead to the production of climate active trace gases such as methylamine and methane. Using radiotracers, we investigated prokaryotic choline/GBT uptake and determined biotic and abiotic factors driving these processes in the Western English Channel, UK. Kinetic uptake parameters indicated high affinity (nM range) for both osmolytes and showed a seasonal pattern for choline uptake. Generalized linear modeling of uptake parameters suggested a significant influence of sea surface temperature and salinity on prokaryotic uptake of both osmolytes. The presence of diatoms significantly influenced prokaryotic choline/GBT uptake dynamics. Choline uptake was further related to the occurrence of Phaeocystis spp., which were highly abundant in the phytoplankton community during spring, and dinoflagellates abundance during summer. While Rhodobacteraceae were the most important bacterial drivers for prokaryotic choline uptake, prokaryotic GBT uptake was associated with various groups such as SAR11 (Pelagibacterales) and Gammaproteobacteria, suggesting a wider capacity for GBT catabolism than previously recognized. Furthermore, using a newly developed approach we determined the first available data for dissolved GBT concentrations in seawater and found both osmolytes to be at the sub‐nanomolar range. Together, this study improves our understanding of the biogeochemical cycling of these environmentally important osmolytes and highlights how their cycles may be affected by a changing climate.

2‐Aminoethylphosphonate utilization in Pseudomonas putida BIRD ‐1 is controlled by multiple master regulators - Andrew R. J. Murphy; David J. Scanlan; Yin Chen; Gary D. Bending; John P. Hammond; Elizabeth M. H. Wellington; Ian D. E. A. Lidbury (Environmental Microbiology, 2022)
Summary Bacteria possess various regulatory mechanisms to detect and coordinate a response to elemental nutrient limitation. In pseudomonads, the two‐component system regulators CbrAB, NtrBC and PhoBR, are responsible for regulating cellular response to carbon (C), nitrogen (N) and phosphorus (P) respectively. Phosphonates are reduced organophosphorus compounds produced by a broad range of biota and typified by a direct C‐P bond. Numerous pseudomonads can use the environmentally abundant phosphonate species 2‐aminoethylphosphonate (2AEP) as a source of C, N, or P, but only PhoBR has been shown to play a role in 2AEP utilization. On the other hand, utilization of 2AEP as a C and N source is considered substrate inducible. Here, using the plant‐growth‐promoting rhizobacterium Pseudomonas putida BIRD‐1 we present evidence that 2AEP utilization is under dual regulation and only occurs upon depletion of C, N, or P, controlled by CbrAB, NtrBC, or PhoBR respectively. However, the presence of 2AEP was necessary for full gene expression, i.e. expression was substrate inducible. Mutation of a LysR‐type regulator, termed AepR, upstream of the 2AEP transaminase‐phosphonatase system (PhnWX), confirmed this dual regulatory mechanism. To our knowledge, this is the first study identifying coordination between global stress response and substrate‐specific regulators in phosphonate metabolism.

Proteomics insights into the Burkholderia cenocepacia phosphorus stress response - Holly Shropshire; Rebekah A. Jones; María M. Aguilo‐Ferretjans; David J. Scanlan; Yin Chen (Environmental Microbiology, 2021)
Summary The Burkholderia cepacia complex is a group of Burkholderia species that are opportunistic pathogens causing high mortality rates in patients with cystic fibrosis. An environmental stress often encountered by these soil‐dwelling and pathogenic bacteria is phosphorus limitation, an essential element for cellular processes. Here, we describe cellular and extracellular proteins differentially regulated between phosphate‐deplete (0 mM, no added phosphate) and phosphate‐replete (1 mM) growth conditions using a comparative proteomics (LC–MS/MS) approach. We observed a total of 128 and 65 unique proteins were downregulated and upregulated respectively, in the B . cenocepacia proteome. Of those downregulated proteins, many have functions in amino acid transport/metabolism. We have identified 24 upregulated proteins that are directly/indirectly involved in inorganic phosphate or organic phosphorus acquisition. Also, proteins involved in virulence and antimicrobial resistance were differentially regulated, suggesting B . cenocepacia experiences a dramatic shift in metabolism under these stress conditions. Overall, this study provides a baseline for further research into the biology of Burkholderia in response to phosphorus stress.

Riding the wave of genomics to investigate aquatic coliphage diversity and activity - Slawomir Michniewski; Tamsin Redgwell; Aurelija Grigonyte; Branko Rihtman; Maria Aguilo‐Ferretjans; Joseph Christie‐Oleza; Eleanor Jameson; David J. Scanlan; Andrew D. Millard (Environmental Microbiology, 2019)
Summary Bacteriophages infecting Escherichia coli (coliphages) have been used as a proxy for faecal matter and water quality from a variety of environments. However, the diversity of coliphages that is present in seawater remains largely unknown, with previous studies largely focusing on morphological diversity. Here, we isolated and characterized coliphages from three coastal locations in the United Kingdom and Poland. Comparative genomics and phylogenetic analysis of phage isolates facilitated the identification of putative new species within the genera Rb69virus and T5virus and a putative new genus within the subfamily Tunavirinae . Furthermore, genomic and proteomic analysis combined with host range analysis allowed the identification of a putative tail fibre that is likely responsible for the observed differences in host range of phages vB_Eco_mar003J3 and vB_Eco_mar004NP2.

Thermoacclimation and genome adaptation of the membrane lipidome in marine Synechococcus - Justine Pittera; Juliette Jouhet; Solène Breton; Laurence Garczarek; Frédéric Partensky; Éric Maréchal; Ngoc A. Nguyen; Hugo Doré; Morgane Ratin; Frances D. Pitt; David J. Scanlan; Christophe Six (Environmental Microbiology, 2018)
Summary The marine cyanobacteria of the genus Synechococcus are important primary producers, displaying a wide latitudinal distribution that is underpinned by diversification into temperature ecotypes. The physiological basis underlying these ecotypes is poorly known. In many organisms, regulation of membrane fluidity is crucial for acclimating to variations in temperature. Here, we reveal the detailed composition of the membrane lipidome of the model strain Synechococcus sp. WH7803 and its response to temperature variation. Unlike freshwater strains, membranes are almost devoid of C18, mainly containing C14 and C16 chains with no more than two unsaturations. In response to cold, we observed a rarely observed process of acyl chain shortening that likely induces membrane thinning, along with specific desaturation activities. Both of these mechanisms likely regulate membrane fluidity, facilitating the maintenance of efficient photosynthetic activity. A comprehensive examination of 53 Synechococcus genomes revealed clade‐specific gene sets regulating membrane lipids. In particular, the genes encoding desaturase enzymes, which is a key to the temperature stress response, appeared to be temperature ecotype‐specific, with some of them originating from lateral transfers. Our study suggests that regulation of membrane fluidity has been among the important adaptation processes for the colonization of different thermal niches by marine Synechococcus .

Comparative genomic, proteomic and exoproteomic analyses of three Pseudomonas strains reveals novel insights into the phosphorus scavenging capabilities of soil bacteria - Ian D. E. A. Lidbury; Andrew R. J. Murphy; David J. Scanlan; Gary D. Bending; Alexandra M. E. Jones; Jonathan D. Moore; Andrew Goodall; John P. Hammond; Elizabeth M. H. Wellington (Environmental Microbiology, 2016)
Summary Bacteria that inhabit the rhizosphere of agricultural crops can have a beneficial effect on crop growth. One such mechanism is the microbial‐driven solubilization and remineralization of complex forms of phosphorus (P). It is known that bacteria secrete various phosphatases in response to low P conditions. However, our understanding of their global proteomic response to P stress is limited. Here, exoproteomic analysis of Pseudomonas putida BIRD‐1 (BIRD‐1), Pseudomonas fluorescens SBW25 and Pseudomonas stutzeri DSM4166 was performed in unison with whole‐cell proteomic analysis of BIRD‐1 grown under phosphate (Pi) replete and Pi deplete conditions. Comparative exoproteomics revealed marked heterogeneity in the exoproteomes of each Pseudomonas strain in response to Pi depletion. In addition to well‐characterized members of the PHO regulon such as alkaline phosphatases, several proteins, previously not associated with the response to Pi depletion, were also identified. These included putative nucleases, phosphotriesterases, putative phosphonate transporters and outer membrane proteins. Moreover, in BIRD‐1, mutagenesis of the master regulator, phoBR , led us to confirm the addition of several novel PHO‐dependent proteins. Our data expands knowledge of the Pseudomonas PHO regulon, including species that are frequently used as bioinoculants, opening up the potential for more efficient and complete use of soil complexed P.

Comparative genomics and mutagenesis analyses of choline metabolism in the marine R oseobacter clade - Ian Lidbury; George Kimberley; David J. Scanlan; J. Colin Murrell; Yin Chen (Environmental Microbiology, 2015)
Summary Choline is ubiquitous in marine eukaryotes and appears to be widely distributed in surface marine waters; however, its metabolism by marine bacteria is poorly understood. Here, using comparative genomics and molecular genetic approaches, we reveal that the capacity for choline catabolism is widespread in marine heterotrophs of the marine Roseobacter clade ( MRC ). Using the model bacterium R uegeria pomeroyi , we confirm that the bet A , bet B and bet C genes, encoding choline dehydrogenase, betaine aldehyde dehydrogenase and choline sulfatase, respectively, are involved in choline metabolism. The bet T gene, encoding an organic solute transporter, was essential for the rapid uptake of choline but not glycine betaine ( GBT ). Growth of choline and GBT as a sole carbon source resulted in the re‐mineralization of these nitrogen‐rich compounds into ammonium. Oxidation of the methyl groups from choline requires formyltetrahydrofolate synthetase encoded by fhs in R . pomeroyi , deletion of which resulted in incomplete degradation of GBT . We demonstrate that this was due to an imbalance in the supply of reducing equivalents required for choline catabolism, which can be alleviated by the addition of formate. Together, our results demonstrate that choline metabolism is ubiquitous in the MRC and reveal the role of Fhs in methyl group oxidation in R . pomeroyi .

Genomic and proteomic characterization of two novel siphovirus infecting the sedentary facultative epibiont cyanobacterium A caryochloris marina - Yi‐Wah Chan; Andrew D. Millard; Peter J. Wheatley; Antony B. Holmes; Remus Mohr; Anna L. Whitworth; Nicholas H. Mann; Anthony W. D. Larkum; Wolfgang R. Hess; David J. Scanlan; Martha R. J. Clokie (Environmental Microbiology, 2015)
Summary A caryochloris marina is a symbiotic species of cyanobacteria that is capable of utilizing far‐red light. We report the characterization of the phages A ‐ HIS 1 and A ‐ HIS 2, capable of infecting A caryochloris . Morphological characterization of these phages places them in the family S iphoviridae . However, molecular characterization reveals that they do not show genetic similarity with any known siphoviruses. While the phages do show synteny between each other, the nucleotide identity between the phages is low at 45–67%, suggesting they diverged from each other some time ago. The greatest number of genes shared with another phage (a myovirus infecting marine S ynechococcus ) was four. Unlike most other cyanophages and in common with the S iphoviridae infecting S ynechococcus , no photosynthesis‐related genes were found in the genome. CRISPR (clustered regularly interspaced short palindromic repeats) spacers from the host A caryochloris had partial matches to sequences found within the phages, which is the first time CRISPR s have been reported in a cyanobacterial/cyanophage system. The phages also encode a homologue of the proteobacterial RN ase T . The potential function of RN ase T in the mark‐up or digestion of cr RNA hints at a novel mechanism for evading the host CRISPR system.

Shedding new light on viral photosynthesis - Richard J. Puxty; Andrew D. Millard; David J. Evans; David J. Scanlan (Photosynthesis Research, 2015)

Functional distinctness in the exoproteomes of marine S ynechococcus - Joseph A. Christie‐Oleza; Jean Armengaud; Philippe Guerin; David J. Scanlan (Environmental Microbiology, 2015)
Summary The exported protein fraction of an organism may reflect its life strategy and, ultimately, the way it is perceived by the outside world. Bioinformatic prediction of the exported pan‐proteome of P rochlorococcus and S ynechococcus lineages demonstrated that (i) this fraction of the encoded proteome had a much higher incidence of lineage‐specific proteins than the cytosolic fraction (57% and 73% homologue incidence respectively) and (ii) exported proteins are largely uncharacterized to date (54%) compared with proteins from the cytosolic fraction (35%). This suggests that the genomic and functional diversity of these organisms lies largely in the diverse pool of novel functions these organisms export to/through their membranes playing a key role in community diversification, e.g. for niche partitioning or evading predation. Experimental exoproteome analysis of marine S ynechococcus showed transport systems for inorganic nutrients, an interesting array of strain‐specific exoproteins involved in mutualistic or hostile interactions (i.e. hemolysins, pilins, adhesins), and exoenzymes with a potential mixotrophic goal (i.e. exoproteases and chitinases). We also show how these organisms can remodel their exoproteome, i.e. by increasing the repertoire of interaction proteins when grown in the presence of a heterotroph or decrease exposure to prey when grown in the dark. Finally, our data indicate that heterotrophic bacteria can feed on the exoproteome of S ynechococcus .

Elemental composition of natural populations of key microbial groups in A tlantic waters - Carolina Grob; Martin Ostrowski; Ross J. Holland; Mikal Heldal; Svein Norland; Egil S. Erichsen; Claudia Blindauer; Adrian P. Martin; Mikhail V. Zubkov; David J. Scanlan (Environmental Microbiology, 2013)
Summary Intracellular carbon ( C ), nitrogen ( N ) and phosphorus ( P ) content of marine phytoplankton and bacterioplankton can vary according to cell requirements or physiological acclimation to growth under nutrient limited conditions. Although such variation in macronutrient content is well known for cultured organisms, there is a dearth of data from natural populations that reside under a range of environmental conditions. Here, we compare C , N and P content of S ynechococcus , P rochlorococcus , low nucleic acid ( LNA ) content bacterioplankton and small plastidic protists inhabiting surface waters of the North and South subtropical gyres and the E quatorial R egion of the A tlantic O cean. While intracellular C : N ratios ranged between 3.5 and 6, i.e. below the R edfield ratio of 6.6, all the C : P and N : P ratios were up to 10 times higher than the corresponding R edfield ratio of 106 and 16, respectively, reaching and in some cases exceeding maximum values reported in the literature. Similar C : P or N : P ratios in areas with different concentrations of inorganic phosphorus suggests that this is not just a response to the prevailing environmental conditions but an indication of the extremely low P content of these oceanic microbes.

Multi‐locus sequence analysis, taxonomic resolution and biogeography of marine Synechococcus - Sophie Mazard; Martin Ostrowski; Frédéric Partensky; David J. Scanlan (Environmental Microbiology, 2012)
Summary Conserved markers such as the 16S rRNA gene do not provide sufficient molecular resolution to identify spatially structured populations of marine Synechococcus , or ‘ecotypes’ adapted to distinct ecological niches. Multi‐locus sequence analysis targeting seven ‘core’ genes was employed to taxonomically resolve Synechococcus isolates and correlate previous phylogenetic analyses encompassing a range of markers. Despite the recognized importance of lateral gene transfer in shaping the genomes of marine cyanobacteria, multi‐locus sequence analysis of more than 120 isolates reflects a clonal population structure of major lineages and subgroups. A single core genome locus, petB , encoding the cytochrome b 6 subunit of the cytochrome b 6 f complex, was selected to expand our understanding of the diversity and ecology of marine Synechococcus populations. Environmental petB sequences cloned from contrasting sites highlight numerous genetically and ecologically distinct clusters, some of which represent novel, environmentally abundant clades without cultured representatives. With a view to scaling ecological analyses, the short sequence, taxonomic resolution and accurate automated alignment of petB is ideally suited to high‐throughput and high‐resolution sequencing projects to explore links between the ecology, evolution and biology of marine Synechococcus .

Basin‐scale distribution patterns of photosynthetic picoeukaryotes along an Atlantic Meridional Transect - Amy R. Kirkham; Ludwig E. Jardillier; Ana Tiganescu; John Pearman; Mikhail V. Zubkov; David J. Scanlan (Environmental Microbiology, 2011)
Summary Photosynthetic picoeukaryotes (PPEs) of a size

Photosynthetic picoeukaryote community structure in the South East Pacific Ocean encompassing the most oligotrophic waters on Earth - Cécile Lepère; Daniel Vaulot; David J. Scanlan (Environmental Microbiology, 2009)
Summary Photosynthetic picoeukaryotes (PPEs), comprising organisms

From small hosts come big viruses: the complete genome of a second Ostreococcus tauri virus, OtV‐1 - Karen D. Weynberg; Michael J. Allen; Kevin Ashelford; David J. Scanlan; William H. Wilson (Environmental Microbiology, 2009)
Summary Ostreococcus tauri virus (OtV‐1) is a large double‐stranded DNA virus and a prospective member of the family Phycodnaviridae , genus Prasinovirus . OtV‐1 infects the unicellular marine green alga O. tauri , the smallest known free‐living eukaryote. Here we present the 191 761 base pair genome sequence of OtV‐1, which has 232 putative protein‐encoding and 4 tRNA‐encoding genes. Approximately 31% of the viral gene products exhibit a similarity to proteins of known functions in public databases. These include a variety of unexpected genes, for example, a PhoH‐like protein, a N ‐myristoyltransferase, a 3‐dehydroquinate synthase, a number of glycosyltransferases and methyltransferases, a prolyl 4‐hydroxylase, 6‐phosphofructokinase and a total of 8 capsid proteins. A total of 11 predicted genes share homology with genes found in the Ostreococcus host genome. In addition, an intein was identified in the DNA polymerase gene of OtV‐1. This is the first report of an intein in the genome of a virus that infects O. tauri. Fifteen core genes common to nuclear‐cytoplasmic large dsDNA virus (NCLDV) genomes were identified in the OtV‐1 genome. This new sequence data may help to redefine the classification of the core genes of these viruses and shed new light on their evolutionary history.

Differential grazing of two heterotrophic nanoflagellates on marine Synechococcus strains - Katrin Zwirglmaier; Ed Spence; Mikhail V. Zubkov; David J. Scanlan; Nicholas H. Mann (Environmental Microbiology, 2009)
Summary Grazing of heterotrophic nanoflagellates on marine picophytoplankton presents a major mortality factor for this important group of primary producers. However, little is known of the selectivity of the grazing process, often merely being thought of as a general feature of cell size and motility. In this study, we tested grazing of two heterotrophic nanoflagellates, Paraphysomonas imperforata and Pteridomonas danica , on strains of marine Synechococcus . Both nanoflagellates proved to be selective in their grazing, with Paraphysomonas being able to grow on 5, and Pteridomonas on 11, of 37 Synechococcus strains tested. Additionally, a number of strains (11 for Paraphysomonas , 9 for Pteridomonas ) were shown to be ingested, but not digested (and thus did not support growth of the grazer). Both the range of prey strains that supported growth as well as those that were ingested but not digested was very similar for the two grazers, suggesting a common property of these prey strains that lent them susceptible to grazing. Subsequent experiments on selected Synechococcus strains showed a pronounced difference in grazing susceptibility between wild‐type Synechococcus sp. WH7803 and a spontaneous phage‐resistant mutant derivative, WH7803PHR, suggesting that cell surface properties of the Synechococcus prey are an important attribute influencing grazing vulnerability.

Diel rhythmicity in amino acid uptake by Prochlorococcus - Isabelle Mary; Laurence Garczarek; Glen A. Tarran; Christian Kolowrat; Matthew J. Terry; David J. Scanlan; Peter H. Burkill; Mikhail V. Zubkov (Environmental Microbiology, 2008)
Summary The marine cyanobacterium Prochlorococcus , the most abundant phototrophic organism on Earth, numerically dominates the phytoplankton in nitrogen (N)‐depleted oceanic gyres. Alongside inorganic N sources such as nitrite and ammonium, natural populations of this genus also acquire organic N, specifically amino acids. Here, we investigated using isotopic tracer and flow cytometric cell sorting techniques whether amino acid uptake by Prochlorococcus is subject to a diel rhythmicity, and if so, whether this was linked to a specific cell cycle stage. We observed, in contrast to diurnally similar methionine uptake rates by Synechococcus cells, obvious diurnal rhythms in methionine uptake by Prochlorococcus cells in the tropical Atlantic. These rhythms were confirmed using reproducible cyclostat experiments with a light‐synchronized axenic Prochlorococcus (PCC9511 strain) culture and 35 S‐methionine and 3 H‐leucine tracers. Cells acquired the tracers at lower rates around dawn and higher rates around dusk despite >10 4 times higher concentration of ammonium in the medium, presumably because amino acids can be directly incorporated into protein. Leucine uptake rates by cells in the S+G 2 cell cycle stage were consistently 2.2 times higher than those of cells at the G 1 stage. Furthermore, S+G 2 cells upregulated amino acid uptake 3.5 times from dawn to dusk to boost protein synthesis prior to cell division. Because Prochlorococcus populations can account from 13% at midday to 42% at dusk of total microbial uptake of methionine and probably of other amino acids in N‐depleted oceanic waters, this genus exerts diurnally variable, strong competitive pressure on other bacterioplankton populations.

Microbial control of phosphate in the nutrient‐depleted North Atlantic subtropical gyre - Mikhail V. Zubkov; Isabelle Mary; E. Malcolm S. Woodward; Phillip E. Warwick; Bernhard M. Fuchs; David J. Scanlan; Peter H. Burkill (Environmental Microbiology, 2007)
Summary Little is known about the dynamics of dissolved phosphate in oligotrophic areas of the world's oceans, where concentrations are typically in the nanomolar range. Here, we have budgeted phosphate uptake by the dominant microbial groups in order to assess the effect of the microbial control of this depleted nutrient in the North Atlantic gyre. Low concentrations (2.2 ± 1.2 nM) and rapid microbial uptake (2.1 ± 2.4 nM day −1 ) of bioavailable phosphate were repeatedly determined in surface waters of the North Atlantic oligotrophic gyre during spring and autumn research cruises, using a radiotracer dilution bioassay technique. Upper estimates of the concentration of bioavailable phosphate were 7–55% of the dissolved mineral phosphate suggesting that a considerable part of the chemically measured nanomolar phosphate was in a form unavailable for direct microbial uptake. A 1:1 relationship ( r 2 = 0.96, P Prochlorococcus phototrophic cyanobacteria, were the two major competing groups for bioavailable phosphate. These heterotrophic bacteria had low nucleic acid content and 60% of them comprised of SAR11 clade cells based on the results of fluorescence in situ hybridization. Each of the two competing bacterial groups was responsible for an average of 45% of the phosphate uptake, while Synechococcus cyanobacteria (7%) and picoplanktonic algae (0.3%) played minor roles in direct phosphate uptake. We have demonstrated that phosphate uptake in the oligotrophic gyre is rapid and dominated by two bacterial groups rather than by algae.

Molecular analysis of picocyanobacterial community structure along an Arabian Sea transect reveals distinct spatial separation of lineages - Nicholas J. Fuller; Glen A. Tarran; Marian Yallop; Karen M. Orcutt; David J. Scanlan (Limnology and Oceanography, 2006)
We investigated the community structure of Synechococcus and Prochlorococcus along a transect in the Arabian Sea during September 2001. The transect spanned contrasting oceanic conditions, allowing investigation of the effects of both horizontal and vertical environmental gradients over relatively large spatial scales on picocyanobacterial population structure. We applied previously developed oligonucleotide probes specific for different Prochlorococcus ecotypes and Synechococcus clades by hybridization to ‘oxygenic phototroph’ 16S ribosomal DNA polymerase chain reaction amplicons. Flow cytometry data showed that, in general, the picocyanobacterial community was dominated by Prochlorococcus in the southern oligotrophic waters and by Synechococcus in the northern mesotrophic waters. Molecular analysis of these picophytoplankton communities, however, revealed more specific spatial separation of lineages along the transect, with Prochlorococcus in southern surface waters being dominated by the high light‐adapted ecotype, while low light‐adapted (LL) ecotypes were confined to deeper waters below the surface‐mixed layer. Interestingly, between Sta. 2 to 4, the LL genotype MIT9303 appeared to be partitioned at the very base of the euphotic zone, beneath other LL genotypes. Most of the central and northern parts of the transect were dominated by Synechococcus genotypes of the clade II lineage. A significant exception was in the mesotrophic upwelling region, where genotypes representative of clades V/VI/ VII dominated. Members of the recently discovered clades IX and X were found in subsurface samples in warm, coastal waters. We propose that discrete differences, both horizontally and vertically, in a suite of environmental parameters along the transect provide optimal growth conditions for specific genotypes in a particular patch of water, giving rise to distinct spatial compartmentalization of picocyanobacterial lineages.

Molecular analysis of photosynthetic picoeukaryote community structure along an Arabian Sea transect - Nicholas J. Fuller; Glen A. Tarran; Denise G. Cummings; E. Malcolm S. Woodward; Karen M. Orcutt; Marian Yallop; Florence Le Gall; David J. Scanlan (Limnology and Oceanography, 2006)
We developed oligonucleotide probes, based on plastid 16S ribosomal DNA (rDNA) sequences, to target 10 different algal classes (Chlorarachniophyceae, Chrysophyceae, Cryptophyceae, Eustigmatophyceae, Pavlovophyceae, Pelagophyceae, Pinguiophyceae, Prasinophyceae [clade VI], Prymnesiophyceae, and Trebouxiophyceae), for use with dot blot hybridization technology. These class‐specific probes were then used to investigate the community structure of photosynthetic picoeukaryotes (≪3 µm) along a transect in the Arabian Sea during September 2001, using hybridization to plastid 16S rDNA polymerase chain reaction amplicons. The transect ranged from oligotrophic open‐ocean waters, just south of the Equator, through mesotrophic and eutrophic waters toward the north coast of Oman, crossing a region of monsoonal upwelling off the Omani northeast coast. Photosynthetic picoeukaryotes in the surface‐mixed layer (SML) and deep chlorophyll maximum ranged from 1.0 x 10 3 cells mL ‐1 in southern oligotrophic waters to almost 30 x 10 3 cells mL ‐1 at the region of upwelling. Chrysophytes were abundant along most of the transect throughout much of the euphotic zone. Prymnesiophytes were abundant in surface waters along much of the transect. By contrast, trebouxiophytes were confined to deeper waters, below the SML. Pelagophytes were found in surface waters that were more mesotrophic, whereas cryptophytes were only detected in the more nutrient‐rich waters at the northern end of the transect, between depths of 20‐30 m. Pinguiophytes were also detected, but only in the warm surface waters off the north coast of Oman. Chlorarachniophytes, eustigmatophytes, pavlovophytes, and clade VI prasinophytes were essentially below detection limits for the entire transect.

Potential photosynthesis gene recombination between Prochlorococcus and Synechococcus via viral intermediates - Gil Zeidner; Joseph P. Bielawski; Michael Shmoish; David J. Scanlan; Gazalah Sabehi; Oded Béjà (Environmental Microbiology, 2005)
Summary Genes ( psbA and psbD ) encoding for photosynthetically important proteins were recently found in a number of cultured cyanophage genomes. This phenomenon may be a beneficial trait to the viruses or their photosynthetic cyanobacterial hosts, or may represent an untapped pool of genes involved in the formation of the photosynthetic apparatus that are prone to lateral gene transfer. Here we show analyses of psbA genes from uncultured environmental viruses and prophage populations. We observe a statistically significant separation between viral genes and their potential Synechococcus hosts’ genes, and statistical analyses under models of codon evolution indicate that the psbA genes of viruses are evolving under levels of purifying selection that are virtually indistinguishable from their hosts. Furthermore, our data also indicate the possible exchange and reshuffling of psbA genes between Synechococcus and Prochlorococcus via phage intermediates. Overall, these observations raise the possibility that marine viruses serve as a potential genetic pool in shaping the evolution of cyanobacterial photosynthesis.

Genetic diversity of marine Synechococcus and co‐occurring cyanophage communities: evidence for viral control of phytoplankton - Martin Mühling; Nicholas J. Fuller; Andrew Millard; Paul J. Somerfield; Dominique Marie; William H. Wilson; David J. Scanlan; Anton F. Post; Ian Joint; Nicholas H. Mann (Environmental Microbiology, 2005)
Summary Unicellular cyanobacteria of the genus Synechococcus are a major component of the picophytoplankton and make a substantial contribution to primary productivity in the oceans. Here we provide evidence that supports the hypothesis that virus infection can play an important role in determining the success of different Synechococcus genotypes and hence of seasonal succession. In a study of the oligotrophic Gulf of Aqaba, Red Sea, we show a succession of Synechococcus genotypes over an annual cycle. There were large changes in the genetic diversity of Synechococcus , as determined by restriction fragment length polymorphism analysis of a 403‐ bp rpoC1 gene fragment, which was reduced to one dominant genotype in July. The abundance of co‐occurring cyanophage capable of infecting marine Synechococcus was determined by plaque assays and their genetic diversity was determined by denaturing gradient gel electrophoresis analysis of a 118‐bp g20 gene fragment. The results indicate that both abundance and genetic diversity of cyanophage covaried with that of Synechococcus . Multivariate statistical analyses show a significant relationship between cyanophage assemblage structure and that of Synechococcus . These observations are consistent with cyanophage infection being a major controlling factor in picophytoplankton succession.

Molecular diversity among marine picophytoplankton as revealed by psbA analyses - Gil Zeidner; Christina M. Preston; Edward F. Delong; Ramon Massana; Anton F. Post; David J. Scanlan; Oded Béjà (Environmental Microbiology, 2003)
Summary Photosynthetic microorganisms play a crucial role in the marine environment. In vast areas of the oceans, marine primary productivity is performed by cells smaller than 2–3 µm (picoplankton). Here, we report on molecular analyses of the conserved photosynthetic psbA gene (coding for protein D1 of photosystem II reaction centre) as a diversity indicator of naturally occurring marine oxygenic picophytoplankton. The psbA genes proved to be good indicators of the presence of a wide variety of photosynthetic marine microbial groups, including new cyanobacterial groups and eukaryotic algae (prasinophytes). Furthermore, using environmental bacterial artificial chromosome (BAC) libraries, we were able to correlate psbA genes with small subunit rRNAs and, therefore, to confirm their phylogenetic affiliation.